SPIRITUAL METER PERSPEKTIF NASRULLAH SEBAGAI PENGUATAN PENDIDIKAN KARAKTER RELIGIUS - Mahardika Ganda Syaifulloh; Abdurrahmansyah Abdurrahmansyah; Faisal Faisal (PAI RAFAH, 2022)
The research title is "Nasrullah's Perspective Spiritual Meter as an Effort to Strengthen Religious Character Education." A spiritual meter is a measuring instrument to determine the position and condition of a certain spiritual soul in a human body. The spiritual meter is important to learn because the source of the emergence of one's character, including the educators and the students comes from thoughts, feelings, and spirituality.The purpose of this study is to determine the Nasrullah's perspective spiritual meter, spiritual meter as an effort to strengthen the education of religious character, and its contribution to overcoming the problems of religious character education. The type of this research is library research, the research instrument is the researcher himself, and the data analysis technique is the content. The primary data of this research is a book entitled "Secrets of Magnet Sustenance" by Nasrullah. Secondary data is in the form of writings such as journals, books, newspapers, and audio and video recordings that are relevant to the topic.Nasrullah's perspective of spiritual meter in religious character education in this study prioritizes three spiritual souls, namely: the spiritual soul of obtrusion, the spiritual soul of exploration, and the spiritual soul of devotion and love. Spiritual meter as an effort to strengthen religious character education in this study prioritizes two spiritual souls, namely the spiritual soul of exploration and the spiritual soul of devotion and love. The contribution of Nasrullah's spiritual meter is in the form of an exercise program based on the spiritual meter of the soul of exploration as well as the spirit of devotion and love. The training program seeks to overcome the problems of religious character education which tend to be in the cognitive aspect.